2021
DOI: 10.3390/ijerph18041632
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Minimum and Maximum Air Temperatures in the Summer on Heat Stroke in Japan: A Time-Stratified Case-Crossover Study

Abstract: An increase in the global surface temperature and changes in urban morphologies are associated with increased heat stress especially in urban areas. This can be one of the contributing factors underlying an increase in heat strokes. We examined the impact of summer minimum air temperatures, which often represent nighttime temperatures, as well as a maximum temperature on a heat stroke. We collected data from the records of daily ambulance transports for heat strokes and meteorological data for July and August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…103 A high proportion of elderly patients are transported by ambulances for heatstroke in Japan. 51 Environments with prolonged extreme heat have been linked to the increasing trend in the number of heatstroke cases among older adults, 44 , 48 , 57 , 104 , 105 with a high risk of symptom onset at home, including bedrooms. 50 A rise in ambient temperature has also been reported to increase the risk of out-of-hospital cardiac arrest.…”
Section: Climate Change and Impact On Healthmentioning
confidence: 99%
“…103 A high proportion of elderly patients are transported by ambulances for heatstroke in Japan. 51 Environments with prolonged extreme heat have been linked to the increasing trend in the number of heatstroke cases among older adults, 44 , 48 , 57 , 104 , 105 with a high risk of symptom onset at home, including bedrooms. 50 A rise in ambient temperature has also been reported to increase the risk of out-of-hospital cardiac arrest.…”
Section: Climate Change and Impact On Healthmentioning
confidence: 99%
“…3 And up to 1.2 billion people worldwide will be at risk of a HS each year by the year 2100 if global warming continues at this rate. 4 Statistical data have shown that the incidences of HS and HS-induced deaths in China are increasing each year. However, the existing data are limited to some cities or provinces with small sample sizes, and large-scale HS epidemiology data are still lacking in our county or elsewhere in China.…”
Section: Introductionmentioning
confidence: 99%
“…Seriously, the morbidity rate of HS rises each year with global warming 3 . And up to 1.2 billion people worldwide will be at risk of a HS each year by the year 2100 if global warming continues at this rate 4 . Statistical data have shown that the incidences of HS and HS‐induced deaths in China are increasing each year.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures are expected to continue to warm over time, and if global warming continues at this rate, up to 1.2 billion people worldwide will be at risk of heatstroke each year by 2100 9 . Many studies have discussed the relationship between maximum temperature and HS, revealing a signi cant correlation between the two 11,12 . That is, high temperatures contribute to the increased incidence of HS 12,13 .…”
Section: Introductionmentioning
confidence: 99%